Mining the Mycobacterium tuberculosis cellular envelope for diagnostic and drug targets - Wolfe, Lisa Marie, author; Dobos, Karen M., advisor; Belisle, John T., committee member; Dow, Steven, committee member; Lewinsohn, David, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2013)
The cellular envelope of Mycobacterium tuberculosis is a highly complex structure containing many lipids, carbohydrates and proteins. Together these components maintain cellular homeostasis and play an active role in the establishment and maintenance of intracellular infection. The World Health Organization estimates that upon exposure, 90% of infected persons will not succumb to active disease and likely remain a potential source of M. tuberculosis transmission upon the emergence of clinical symptoms. Throughout this complex disease course, physiological and structural changes occur within the cell envelope of the bacillus and facilitate its survival within an infected host. These physiological changes also influence the immunological interplay between bacteria and host cell, further contributing to the success of the pathogen. To understand these changes we must have a comprehensive knowledge of the cell wall proteins that contribute to the overall makeup of the mycobacterial envelope, understand the unique antigens that reside in or that are secreted from the bacillus and monitor these proteins under different physiological disease profiles. In the last decade many large-scale descriptive studies focusing on gene transcript profiles and proteomic composition of subcellular fractions have pioneered efforts in the understanding of M. tuberculosis physiology, immunology and pathogenesis at the level of systems biology. These studies have shown that M. tuberculosis is capable of retaining essential gene products for respiration, nutrient uptake and energy metabolism both in vitro and in vivo and that the proteins within the cell wall are highly immunogenic for M. tuberculosisspecific T lymphocytes. Our first objective established a comprehensive description of the cell wall proteome of M. tuberculosisusing traditional two-dimensional gel-based techniques and liquid-chromatogoraphy mass spectrometry (LC-MS). From this work, over 500 proteins were identified using a combination of differential detergent extraction and multi-dimensional-LC. A highly lipoprotein enriched fraction revealed that the majority of cell wall associated proteins were functionally annotated to mechanisms of intermediary metabolism (35%) and macromolecular synthesis and degradation (25%) building upon evidence that the M. tuberculosis cell wall is actively engaged in cellular homeostasis and remodeling events. Secondly, we investigated the role of the cell envelope proteins in the search for novel immunodiagnostic epitopes. It is well known that the cell wall of M. tuberculosis is highly immunogenic and contains both non-protein and protein antigens. Specifically, the proteins associated with the cell wall were shown to be uniquely responsible for the activation of human CD8 T cell clones generated from both actively and latently infected individuals. The immunological response to CD8 T cell antigens may be an effective means of distinguishing between latent TB infection (LTBI) and active disease. To broadly define the repertoire of CD8 T cell antigens, 56 proteins from the cell wall proteome study were included in the design of a synthetic peptide library. Exhaustive screening of the peptide library for novel antigens and epitopes that elicit an immunological response in TB patients, resulted in the identification of eight cell wall antigens that are currently being investigated for their clinical utility. In addition, the cell wall proteome was also mined in the identification of an HLA-E restricted CD8 T cell epitope. HLA-E has low polymorphism in the human population and seems to be enriched in M. tuberculosis - containing phagosomes, therefore identification of this antigen could be used as a novel diagnostic or vaccine candidate. Using a MS-based proteomics approach, we discovered the HLA-E antigen to be the post-translationally modified glycoprotein Mpt32 (45kDa/Apa). Glycosylated proteins and lipids within the mycobacterial cell envelope are dominant and the role of this modification in the host immune response can now be elucidated. Lastly, the composition and integrity of the M. tuberculosiscell envelope facilitates its adaptation and survival within various microenvironments. These physiological functions are influenced by the presence or absence of functionally linked genes and proteins whose relative abundance may change over time or within altered metabolic states. Our final efforts used nucleotide analog probes, to specifically bind and enrich proteins with an ATP-binding function and measure their relative abundance between altered states of growth (i.e. between active disease and hypoxia-induced dormancy). With these efforts we classified 122 ATP-binding proteins in either metabolic state and demonstrated differential abundance patterns between actively growing and hypoxic cells within the functionally linked protein networks of energy metabolism, cell wall and lipid biosynthesis. These protein families represented in the M. tuberculosis ATPome are a subset of essential (60% of the Mtb-ATPome) gene products and may be relevant therapeutic targets for the future development of novel small molecule inhibitors against M. tuberculosis. The spectrum of studies undertaken to mine the cellular envelope for diagnostic and drug targets demonstrates a natural evolution of MS-based proteomics in the study of biologically relevant questions. From a purely descriptive characterization of the cell wall proteome, this data was utilized in a practical approach in the design of a high-throughput antigen/epitope-screening library and finally these studies culminate in a functionally relevant profile of the ATP-binding proteins of M. tuberculosis. Future work will continue to focus on developing hypothesis-driven proteomic studies for the identification of novel diagnostic antigens and drug targets.
Keywords: cell envelope; proteomics; mass spectrometry; Mycobacterium tuberculosis